A Mathematical Model For Maximum Likelihood Estimation To Atrazine Inhibits Pulsatile Gonadotropin-Releasing Hormone In Animals (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this study, we present a Extreme possibility estimation to analyze examine the strong ATR doses can work  hypothalamic GnRH inhabiting life unlocks  patterns in a style that is exactly the same as seen in the LH   secretion.  In presentation, inflammatory hormone levels  are likely to work in response to GnRH. Finally, we decide that a computational model is based on the submission portion and we result with the medical refort . This paper will be very useful in the future for  medical field.